2013
DOI: 10.1088/0169-5983/45/4/045504
|View full text |Cite
|
Sign up to set email alerts
|

Particle image velocimetry technique measurements of the near wake behind a cylinder-pair of unequal diameters

Abstract: The wake structure behind a circular cylinder-pair of unequal diameters as a function of incident flow angle α (0 • α 180 • ) has been investigated using the particle image velocimetry technique. The Reynolds number Re, centerto-center spacing ratio (P/D) and diameter ratio (d/D) are kept constant at 1200, 1.2 and 2/3, respectively. Instantaneous vorticity contours, mean flow fields and Reynolds shear stress contours are presented to elucidate the flow characteristics. The flow patterns behind the cylinder-pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Meanwhile, the vortexes from base flow pass through the spacing and also contribute to the high intensity here. The same intensity distribution can be seen in the near wake flow of a cylinder-pair [39]. This formation mechanism for grid-generated turbulence is distinguished from that reflected by smoke wires [40], which is mostly due to the different Reynold number and base flow regime.…”
Section: Turbulent Flowmentioning
confidence: 61%
“…Meanwhile, the vortexes from base flow pass through the spacing and also contribute to the high intensity here. The same intensity distribution can be seen in the near wake flow of a cylinder-pair [39]. This formation mechanism for grid-generated turbulence is distinguished from that reflected by smoke wires [40], which is mostly due to the different Reynold number and base flow regime.…”
Section: Turbulent Flowmentioning
confidence: 61%
“…The LaVision Davis software (Davis 8.2.3) was used to process the raw particle images and determine the flow vector fields through the fast-Fourier-transform (FFT) method based on cross correlation algorithm with the standard Gaussian sub-pixel fit structured as an iterative multi-grid method. The processing procedure included two passes, starting with the interrogation window consisted of 64×64 pixels (8 mm×8 mm or 0.4D×0.4D) with a 50% overlap, and then stepping down to 32×32 pixels (4 mm×4 mm or 0.2D×0.2D) with a 50% overlap, corresponding to 128×128 velocity vectors (namely, spatial resolution of 2 mm×2 mm) obtained in the viewing area, more details of PIV measurement system and data processing were presented by Gao et al (2013). For each case, a total of 6500 PIV images were captured, yielding about 70 vortex shedding cycles for an isolated cylinder (Strouhal number St=0.2) at low Reynolds number Re=1500, and more than 230 vortex shedding cycles at high Reynolds number Re=5000.…”
Section: Experimental Set-upmentioning
confidence: 99%
“…It was also found that the vortical wake of the upstream cylinder causes a restoring force on the downstream cylinder, which is equivalent to a linear spring, hence affecting its natural frequency [3]. In the few studies conducted with interfering cylinders of unequal diameter [115,82,40,41,39], it was found that the upstream cylinder also affects the response of the downstream cylinder, reducing its amplitude relative to the single cylinder case, while the frequency of oscillation of the downstream cylinder was found to be either equal to, or twice the value of the frequency of the upstream cylinder. Only one published study [91] has begun to show the harbor seal whiskers' response under WIV conditions.…”
Section: Motivationmentioning
confidence: 99%